Radiology Fundamentals : Introduction to Imaging & Technology - Singh, Harjit; Neutze, Janet A.; Enterline, Jonathan R. (Springer International Publishing : Imprint: Springer, 2015)
This book is a concise introduction to the dynamic field of radiology and provides readers with general examples and brief discussions of basic radiographic principles. Introductory chapters present fundamental scientific concepts underlying the medical use of imaging modalities and technology, including ultrasound, computed tomography, magnetic resonance imaging, and nuclear medicine.  Subsequent chapters are organized by anatomic region and imaging modality that highlight the radiologist's role in diagnosing and treating common disorders. This revised edition is thoroughly updated and includes new or expanded chapters on nuclear medicine and pediatric radiology. Radiology Fundamentals, Fifth Edition, is a premier self-directed learning resource for medical students, non-radiology housestaff, physician assistants, nurse practitioners, radiologist assistants and other allied health professionals.